CHANGE IN TECTONIC ACTIVITY OF THE EARTH IN THE LAST 150 MILLION YEARS - Zonenshayn L.P.; Khain V.V. (My University, 1989)
It has long been known that the tectonic activity of the Earth varies significantly with time. The best method of estimating tectonic activity is to calculate the amount of ocean crust accreted along spreading axes on a global scale. To compute the present area of crustal accretion, we used the parameters of global plate movements. The coordinates of the initial and end points of the spreading axes were taken from the map of present plate boundaries. The present overall crustal accretion rate is 2.9 (more accurately 2.909) km 2·yr -1-0.5 km ·yr -1 from the Atlantic, 0.8 for the Indian Ocean and 1.6 for the Pacific. Our calculations show that the tectonic activity index in the last 150 m.y. did not fluctuate more than twice and varied within the range from 0.8 to 1.6. This two-fold fluctuation in global tectonic activity should be regarded as the limit of its variation at least for the Phanerozoic.